2016
DOI: 10.1051/matecconf/20168501014
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of natural zeolites for the development of new materials: short review

Abstract: Abstract. Zeolites stand apart among the many families of porous materials. Due to their structure, they have a number of important practical properties such as a high adsorption capacity and the ability to cation exchange. However, the main feature distinguishing them from other porous bodies and inherent only for zeolites is the ordering of the pores in their size, orientation, and mutual locations. Pore diameters for the crystalline structures of various zeolites may vary from 0.25 to about 15 nanometers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Natural zeolite is found all over the world. Although there are no accurate data on the total amount of zeolites, it is reported that they occur on all continents with different mineral concentrations and types [34]. Natural zeolites are produced by the interaction of volcanic rock and volcanic ash with alkaline groundwater, usually related to mountainous areas such as the Caucasus and Balkans.…”
Section: Natural Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural zeolite is found all over the world. Although there are no accurate data on the total amount of zeolites, it is reported that they occur on all continents with different mineral concentrations and types [34]. Natural zeolites are produced by the interaction of volcanic rock and volcanic ash with alkaline groundwater, usually related to mountainous areas such as the Caucasus and Balkans.…”
Section: Natural Zeolitesmentioning
confidence: 99%
“…Natural zeolites are used for wide applications due to its low cost and availability, on the other hand, the industrial application of natural zeolite is limited because, as mentioned above, its properties strictly depend on its crystal structure. The main disadvantage is that the channel diameter is too small to absorb larger gas molecules and organic compounds [34]. Furthermore, zeolites, due to the very different conditions under which they are formed in nature, are rarely pure but contaminated to varying degrees by other minerals, metals, quartz, or other zeolites [7].Therefore, natural zeolite is excluded from many important commercial applications where uniformity and purity are essential [35].…”
Section: Natural Zeolitesmentioning
confidence: 99%
“…W środowisku naturalnym powstają wskutek działalności wulkanicznej. Posiadają strukturę szkieletową zawierającą wolne przestrzenie (przestrzenie te wypełniają duże jony i cząsteczki wody), co sprawia, że posiadają dużą pojemność sorpcyjną, aktywność katalityczną oraz wysoki poziom selektywności jonowymiennej, która stanowi jedną z podstawowych cech charakteryzujących zeolity naturalne i syntetyczne [2]. Wolne przestrzenie w zeolitach mają postać różnorakich kanałów i komór, a znajdując się w cząsteczkach wody mogą swobodnie się poruszać.…”
Section: Zeolit -Jego Budowa I Właściwościunclassified
“…Natural zeolite deposits found across all continents display various mineral content and types, but there are no accurate statistics on the world reserves [ 30 , 31 ]. About 70 types of natural zeolite occur worldwide, and more than 250 zeolites similar to the natural ones have been synthesized.…”
Section: Introductionmentioning
confidence: 99%